Experimental evaluation scheme of ultra-wideband human body transmission model for wireless body area network - Chaisang, Aditep; Promwong, Sathaporn (My University, 2018)
The body area network (BAN) working on IEEE 802.15.6 is a wireless short-range communication system that is smaller in coverage than the personal area network (PAN) IEEE802.15.3a. A wireless body area network (WBAN) is a wireless technology with a human body that is becoming a key part of short-range radio wave systems and wireless medical technology. The transfer function characteristics of the human body and the transmission loss due to the human body should be studied. Short-range radio wave applications with a human body are more complicated than additional uses. Therefore, realizing the distribution channel characteristics of the human body with ultra-wideband (UWB) technology is important. UWB technology has a very large bandwidth, low power, and low cost, which can be used in shortrange systems. In this paper, we present the characterization measurement data of the UWBHB channel transfer function based on the human body effect with and without human body in WBAN system. In this study, we maximize the signal-to-noise ratio (SNR) and contemplate the matched filter at the receiver. The outcomes are analyzed and evaluated on the basis of Friis' formula. The proposed method achieves very precise results and is convenient for the evaluation and design of the waveform of WBAN transmission in wireless medical applications and BAN systems, mainly focusing on the input waveform effect.
Keywords: Impulse radio; UWB; UWB-HB; UWB-IR; WBAN